Copolyester nanocomposites based on carbon nanotubes: reinforcement effect of carbon nanotubes on viscoelastic and dielectric properties of nanocomposites - Kalgaonkar, Rajendra A.; Jog, Jyoti Prakash (Polymer International, 2008)
Nanocomposites based on an amorphous copolyester, poly(ethylene glycol-co-cyclohexane-1,4-dimethanol terephthalate) and carbon nanotubes were fabricated using a simple melt processing technique. The reinforcement effect of carbon nanotubes in the copolyester was investigated experimentally using different approaches based on dynamic mechanical analysis, theology and dielectric analysis. The nanocomposites show a mechanical reinforcement effect with significant increase in the stiffness especially in the rubbery regime with increasing nanotube content. An increase in T-g and a decrease in damping are seen, which are derived from the presence of a percolating superstructure of the filler. Rheological experiments show an increase in storage modulus up to four orders of magnitude. Viscolelastic characterization shows that the percolation threshold is at 3 wt% of nanotubes. Dielectric relaxation spectroscopy confirms the presence of this percolating structure. We conclude that the responses of both rheological and electrical properties are different, although both are related to the formation of a percolating network superstructure of the filler. (c) 2007 Society of Chemical Industry.
Keywords: Carbon nanotubes; dielectric analysis; nanocomposites.; reinforcement; viscoelastic properties

Molecular dynamics of copolyester/clay nanocomposites as investigated by viscoelastic and dielectric analysis - Kalgaonkar, Rajendra A.; Jog, Jyoti Prakash (Journal of Polymer Science Part B-Polymer Physics, 2008)
We have investigated the molecular dynamics of poly(ethylene glycol-co-cycloxeane-1,4-dimethanol terephthalate) (PETG) nanocomposites based on a organically modified layered silicate. Intercalated namocomposites were prepared by melt compounding technique as evidenced from the X-ray diffraction and transmission electron microscopy studies. Two relaxation processes were observed in pure PETG as well as in the nanocomposites. The low-temperature beta-process was assigned to the local motions of C=O polar groups and the alpha-process was due to the glass-rubber transition or the segmental relaxations associated with the polymer chain backbone. Presence of layered silicates accelerated alpha-relaxation dynamics in the nanocomposites accompanied by a depression in T(g) which was attributed to the reduced intermolecular cooperativity between intercalated polymers chains. Additionally, a direct comparison between the viscoelastic and dielectric studies shows excellent agreement between the accelerated alpha dynamics of the nanocomposites. (C) 2008 Wiley Periodicals, Inc. J Polym Sci Part B: Polym Phys 46: 2539-2555, 2008
Keywords: clay; Dielectric relaxation; Nanocomposites; polyesters